Micromilling of Ti6Al4V alloy assisted by plasma electrolytic oxidation. (2nd December 2020) - Hu, Yizhong; Meng, Jianbing; Luan, Xiaosheng; Dong, Xiaojuan; Zhou, Haian; Qu, Linghui; Zhang, Hongwei; Wei, Xiuting
Abstract: This paper develops a novel processing method of plasma electrolytic oxidation-assisted micromilling (PEOAM). Electrolyte solutions with KH2 PO4, NaAlO2, or Na2 SiO3 as the main component are designed, and three types of oxide films are grown on the surface of a Ti6Al4V alloy in situ by means of plasma electrolytic oxidation. The morphology and composition of the oxide films are characterized by scanning electron microscope and energy dispersive spectrum. Additionally, the cutting force and surface roughness of PEOAM are measured by dynamometer and white light interferometer, respectively. A comparison between PEOAM and conventional micromilling in terms of cutting force, tool wear, chips, and surface roughness is conducted, with results showing that oxide films with about 20 μ m thickness are loose and porous, their hardness decreasing to a minimum of 1.12 GPa, which corresponds to 23.3% of the original hardness value. At the axial cutting depth of 18 μ m, compared to the Fx, Fy, and Fz values of the Ti6Al4V alloy substrate, the average milling forces of the NaAlO2 oxide film are the most significantly reduced (35.1%, 15.7%, and 94.8% of the original values, respectively). At the axial cutting depth of 25 μ m, the surface roughness ( R a ) value of PEOAM is reduced by 0.08–0.12 μ m. Consequently, under the same cutting parameters, PEOAM can effectively reduce the cutting force, prolong the service life of the tool, and improve surface quality.